The Association Between the Knowledge and Self-Medication Practices for Upper Respiratory Tract Infection (URTI) in the DKI Jakarta Population - Nathanael, Kevin; Jonlean, Reganedgary; Gayatri, Anggi (Generics: Journal of Research in Pharmacy, 2025)
Most upper respiratory infections (URTIs) are caused by viruses and are self-limiting. It is one of the most frequent diseases to be treated with self-medication. Approriate self-medication practices will increase the safety of drug use. These practices need to be supported by a good level of knowledge. Therefore, this study was aimed to assess the association between level of knowledge and self-medication practices for URTIs in DKI Jakarta population. This cross-sectional study used an online questionnaire distributed around DKI Jakarta. The answers given by the subjects in the questionnaire will be used as our primary data, and the sample population was comprised of adult residents of DKI Jakarta. The questionnaire was developed by the study team and had been tested for validity and reliability before being used for data collection9. The questionnaire was divided into 3 parts, for collecting demographic data, self-medication patterns and level of knowledge regarding self-medication in URTIs. A Chi Square test was performed to analyze the association between level of knowledge and appropriateness of self-medication practices, with p value = 0.05. A total of 102 participants were analyzed at the end of this study. Information from peers tends to be the source of information for most participants, with 73.5% from friends and neighbors and 84.3% from family members. Only 21.6% of participants sought information from medical professionals. As many as 91.2% of participants took antibiotics to relieve their symptoms of URTI without prescription. Most subjects had an adequate level of knowledge (51%) and only a few subjects had a poor level of knowledge (4.9%). There was no significant association between the level of knowledge and the appropriateness of selecting drugs to treat fever, cough and rhinorrhea in this study. Most of the participants have an adequate level of knowledge on self-medication for URTI symptoms. However, there was no association between level of knowledge and the appropriateness of drug selection and the consumption of antibiotics without doctor prescription is still a common practice